THE ORDER OF GENERATION AND DISPOSAL OF EXISTING WASTE IN SURKHANDARYA (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
This article examines the issues related to waste generation and disposal in Surkhandarya, a region in southern Uzbekistan. It explores the current waste management practices, their environmental impact, and proposes sustainable solutions to address the challenges. The study incorporates literature analysis, data collection, and expert opinions to present a comprehensive overview of the situation.